Question

i faced a expression which is below

A ∨ (B ∧ C) ∨ (D ∧ E ∧ ¬ (A ∨ B))

how to Convert into CNF(Conjunctive normal form)?

Was it helpful?

Solution

Assuming you want an equivalent formula you have to use transformations that preserves logical equivalence.

Here is a potential first step;

A ∨ (B ∧ C) ∨ (D ∧ E ∧ ¬(A ∨ B))
((A ∨ B) ∧ (A ∨ C)) ∨ (D ∧ E ∧ ¬A ∧ ¬B)

Taking distribution laws for A ∨ (B ∧ C) and applying DeMorgan to ¬(A ∨ B)

Licensed under: CC-BY-SA with attribution
Not affiliated with StackOverflow
scroll top